2017
DOI: 10.1109/lra.2017.2720851
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Quadrotor With Reinforcement Learning

Abstract: Abstract-In this paper, we present a method to control a quadrotor with a neural network trained using reinforcement learning techniques. With reinforcement learning, a common network can be trained to directly map state to actuator command making any predefined control structure obsolete for training. Moreover, we present a new learning algorithm which differs from the existing ones in certain aspects. Our algorithm is conservative but stable for complicated tasks. We found that it is more applicable to contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
277
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(280 citation statements)
references
References 16 publications
2
277
0
1
Order By: Relevance
“…This idea can be applied to other modules as well. Instead of a traditional proportional-integral-derivative (PID) control design, a network can map from a robot's state to motor commands (107). More ambitiously, some works have mapped directly from camera inputs to motor commands (108)(109)(110) and demonstrated navigation through indoor hallways and forests.…”
Section: Learningmentioning
confidence: 99%
“…This idea can be applied to other modules as well. Instead of a traditional proportional-integral-derivative (PID) control design, a network can map from a robot's state to motor commands (107). More ambitiously, some works have mapped directly from camera inputs to motor commands (108)(109)(110) and demonstrated navigation through indoor hallways and forests.…”
Section: Learningmentioning
confidence: 99%
“…Moreover, a zero convergence proof of the control errors was included and it was validated through numerical simulations. In addition, other control approaches have been used for multicopters navigation such as predictive control, 3 sliding-mode control approach, 4 and NN trained using reinforcement learning techniques, 5 inverse dynamic, 6 and inverse kinematics considering energy consumption. 7 Therefore, the great challenge of how to effectively control a UAV to precisely track a desired trajectory is still subject to active research in UAV control.…”
Section: Motivationmentioning
confidence: 99%
“…Sutton et al [7] have shown that RLC is direct adaptive optimal control, and that the system will converge to the optimal solution given infinite amount of trials. Hwangbo et al [11] have shown an example of training a controller for stabilizing a quad rotor using RLC. The RLC directly mapped the state of the quad rotor to actuator command, making any predefined control structure obsolete.…”
Section: Reinforcement Learning Controlmentioning
confidence: 99%